Does deprivation index modify the acute effect of black smoke on cardiorespiratory mortality? - Carder, M.; McNamee, R.; Beverland, I.; Elton, R.; Cohen, G.; Boyd, James; Van Tongeren, M.; Agius, R. (BMJ Group, 2010)
Objectives: To investigate whether deprivation index modifies the acute effect of black smoke on cardiorespiratory mortality. Methods: Generalised linear Poisson regression models were used to investigate whether deprivation index (as measured by the Carstairs deprivation index) modified the acute effect of black smoke on mortality in two largest Scottish cities (Glasgow and Edinburgh) between January 1981 and December 2001. Lag periods of up to 1 month were assumed for the effects of black smoke. Results: Deprivation index significantly modified the effect of black smoke on mortality, with black smoke effects generally increasing as level of deprivation increased. The interaction coefficient from a parametric model assuming a linear interaction between black smoke (µg/m-3) and deprivation in their effect on mortalitydequivalent to a test of 'linear trend' across Carstairs categoriesdwas significant for all mortality outcomes. In a model where black smoke effects were estimated independently for each deprivation category, the estimated increase in respiratory mortality over the ensuing 1-month period associated with a 10 µg/m3 increase in the mean black smoke concentration was 8.0% (95% CI 5.1 to 10.9) for subjects residing in the 'most' deprived category (Carstairs category 7) compared to 3.7% (95% CI -0.7 to 8.4) for subjects residing in the 'least' deprived category (Carstairs category 1). Conclusions: The results suggest a stronger effect of black smoke on mortality among people living in more deprived areas. The effect was greatest for respiratory mortality, although significant trends were also seen for other groups. If corroborated, these findings could have important public health implications.